From hydrogen to helium: the spectral evolution of white dwarfs as evidence for convective mixing. Issue 3 (21st January 2020) - Cunningham, Tim; Tremblay, Pier-Emmanuel; Gentile Fusillo, Nicola Pietro; Hollands, Mark; Cukanovaite, Elena
ABSTRACT: We present a study of the hypothesis that white dwarfs undergo a spectral change from hydrogen- to helium-dominated atmospheres using a volume-limited photometric sample drawn from the Gaia- DR2 catalogue, the Sloan Digital Sky Survey (SDSS), and the Galaxy Evolution Explorer ( GALEX ). We exploit the strength of the Balmer jump in hydrogen-atmosphere DA white dwarfs to separate them from helium-dominated objects in SDSS colour space. Across the effective temperature range from 20 000 to 9000 K, we find that 22 per cent of white dwarfs will undergo a spectral change, with no spectral evolution being ruled out at 5σ. The most likely explanation is that the increase in He-rich objects is caused by the convective mixing of DA stars with thin hydrogen layers, in which helium is dredged up from deeper layers by a surface hydrogen convection zone. The rate of change in the fraction of He-rich objects as a function of temperature, coupled with a recent grid of 3D radiation-hydrodynamic simulations of convective DA white dwarfs – which include the full overshoot region – lead to a discussion on the distribution of total hydrogen mass in white dwarfs. We find that 60 per cent of white dwarfs must have a hydrogen mass larger than M H / M WD  = 10 −10, another 25 per cent have masses in the range M H / M WD  = 10 −14 –10 −10, and 15 per cent have less hydrogen than M H / M WD  = 10 −14 . These results have implications for white dwarf asteroseismology, stellar evolution through the asymptotic giant branch and accretion of planetesimals on to white dwarfs.